Synthesis of biologically-active reduced graphene oxide by using fucoidan as a multifunctional agent for combination cancer therapy. (27th September 2018) - Kang, Seounghun; Hong, Yu Lim; Ku, Bon-Cheol; Lee, Seunghyun; Ryu, Seongwoo; Min, Dal-Hee; Jang, Hongje; Kim, Young-Kwan
Abstract: A therapeutic reduced graphene oxide (RGO) is synthesized by using fucoidan (Fu) as the reducing and surface functionalizing agent. The synthesized Fu–RGO exhibits promising characteristics for therapeutic applications such as high dispersity in aqueous media, biocompatibility, selective cytotoxicity to cancer cells, high loading capacity of the anticancer drug, and photothermal conversion effect. Therefore, Fu–GO is successfully harnessed as a combinatorial cancer treatment platform through bio-functional (Fu), chemo (doxorubicin (Dox)) and photothermal (RGO with near-infrared irradiation) modalities.